Molecular Imaging of Biological Gene Delivery Vehicles for Targeted Cancer Therapy: Beyond Viral Vectors - Min, Jung-Joon (Springer-Verlag, 2010)
Cancer persists as one of the most devastating diseases in the world. Problems including metastasis and tumor resistance to chemotherapy and radiotherapy have seriously limited the therapeutic effects of present clinical treatments. To overcome these limitations, cancer gene therapy has been developed over the last two decades for a broad spectrum of applications, from gene replacement and knockdown to vaccination, each with different requirements for gene delivery. So far, a number of genes and delivery vectors have been investigated, and significant progress has been made with several gene therapy modalities in clinical trials. Viral vectors and synthetic liposomes have emerged as the vehicles of choice for many applications. However, both have limitations and risks that restrict gene therapy applications, including the complexity of production, limited packaging capacity, and unfavorable immunological features. While continuing to improve these vectors, it is important to investigate other options, particularly nonviral biological agents such as bacteria, bacteriophages, and bacteria-like particles. Recently, many molecular imaging techniques for safe, repeated, and high-resolution in vivo imaging of gene expression have been employed to assess vector-mediated gene expression in living subjects. In this review, molecular imaging techniques for monitoring biological gene delivery vehicles are described, and the specific use of these methods at different steps is illustrated. Linking molecular imaging to gene therapy will eventually help to develop novel gene delivery vehicles for preclinical study and support the development of future human applications.